2021
DOI: 10.1371/journal.pone.0245764
|View full text |Cite
|
Sign up to set email alerts
|

Does perfusion computed tomography correlate to pathology in colorectal liver metastases?

Abstract: Introduction Targeted therapy against tumor angiogenesis is widely used in clinical practice for patients with colorectal liver metastases (CRLM). Possible predictive biomarkers for tumor angiogenesis, such as, microvessel density (MVD), hypoxia and cell proliferation, can be determined using immunohistochemical staining. However, patients ineligible for surgical treatment need to undergo invasive diagnostic interventions in order to determine these biomarkers. CT perfusion (CTP) is an emerging functional imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A previous study ( 29 ) found that the central area of liver metastases primarily consists of necrotic tissue and a small number of tumor cells, with mainly tumor cells and new capillaries at the periphery; as a result, most liver metastases show ring enhancement on contrast-enhanced CT images. ROI visualization results showed that the model’s decision basis for predicting HER2 status was mostly located at the tumor margin, which is consistent with previous reports that metastatic tumor cells are primarily located at the edge of the lesion.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study ( 29 ) found that the central area of liver metastases primarily consists of necrotic tissue and a small number of tumor cells, with mainly tumor cells and new capillaries at the periphery; as a result, most liver metastases show ring enhancement on contrast-enhanced CT images. ROI visualization results showed that the model’s decision basis for predicting HER2 status was mostly located at the tumor margin, which is consistent with previous reports that metastatic tumor cells are primarily located at the edge of the lesion.…”
Section: Discussionmentioning
confidence: 94%